Variation in biomass related variables of reed canary grass - SAHRAMAA, M.; IHAMÄKI, H.; JAUHIAINEN, L. (Agricultural and Food Science, 2003)
Reed canary grass, Phalaris arundinacea L., is a relatively new biomass crop in northern Europe, which produces raw material for bioenergy and paper pulp. Breeding reed canary grass for industrial purposes is under way in the absence of domestic cultivars being available. Knowledge of the extent of variation in biomass related traits is a basic requirement of the breeding programme. The aim of this study was to describe variation in biomass related traits and evaluate the relationships among the variables. Field experiment was carried out between 1994 and 1998 in Finland. Research material included wild and elite populations, which were divided into ten groups according to their origin. Biomass yield, plant fractions, shoot number, node number, leaf area and overwintering ability were measured. Panicle number, plant height and seed ripening were included to the analyses of the relationships. Results indicated the high biomass yield potential of reed canary grass, reaching over 13 t DM ha-1 in the fourth year after establishment. Elite material and a local group from southern Finland had the highest biomass yield, whereas the northernmost local group had the lowest. Three factors established accounted for 45% of the variance and they were defined as high biomass yield, leaf-shoot relationship and fast development. The first factor indicated positive connections among biomass yield, panicle number, plant height, straw fraction and node fraction. This study indicated variation in agronomic traits of reed canary grass, which enables breeding of new cultivars with desired trait combinations.;